Original Minority: The Screenplay Based on the Literary Text (“Intermezzo” by Serhii Parajanov) - Nataliia Nikoriak (Pitannâ Lìteraturoznavstva, 2017)
A screenplay, being a new and objectively separate form of the modern art and at the same time a new type of text, takes an autonomous niche in the literary canon. Though and nowadays too little scientific attention is paid to the script legacy of one writer/scenarist/artist or another. Normally screenplays are incorporated into the complete works of a writer on the rights of addendum to the main body of texts as merely a minor work in spite of the fact that a screenplay can be written more masterly than its film interpretation. If it comes to an editor or a scenarist who did not manifest themselves actively on the field of literature then their texts can be found at best in collections of screenplays or in archives in typewritten form albeit the texts as separate creations can appear really valuable from the aesthetic standpoint. Even more complicated situation is with a screenplay-interpretation of a literary text: first of all because of uncertainty of the status it does not just stay on peripheries of the genre hierarchy but is ignored as a text.